Efficacy of Combination Therapy with Alpha-1 Blocker and 5-Phosphodiesterase Inhibitor in Patients with Benign Prostatic Hyperplasia Associated Lower Urinary Tract Symptoms (Luts) - Sheikh Muhammad Sajid Ali; Asim, Muhammad; Murtaza, Yasir; Ahmed, Syed Farhan; Memon, Waqas; Rashid, Muhammad; Memon, Imran (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the effectiveness of Alpha-1 Blocker in combination with Phosphodiesterase-5 Inhibitor versus Alpha-1 Blocker alone for the management of lower urinary tract symptoms in patients with Benign Prostatic Hyperplasia. Material and Methods: A quasi-experimental study was undertaken at the Urology Department, Liaquat National Hospital, Karachi between May 2018 to November 2019. About sixty patients with benign prostatic hyperplasia and correlated lower urinary tract symptoms were included. The participants were distributed into two groups (Group A was prescribed combined therapy while Group B was prescribed monotherapy). The therapy was considered as successful if there was an improvement in the International Prostate symptom scoring of more than 3 points from the baseline to 12 weeks. Statistical analysis was performed using Excel sheet and SPSS v. 26. Results: In group 1 (combined therapy), 22 (73.3%) (22/30) of the patients reported a significant reduction in International Prostate symptom scores after taking Tamsulosin with Sildenafil as compared to Group 2, where only 13 (43.3%) patients who were treated with Tamsulosin only reported improvement in the International Prostatic symptom scoring at 12 weeks of treatment. Conclusion: The current study indicates that Tamsulosin in combination with Sildenafil is more effective in relieving the lower tract urinary symptoms in patients with benign prostate hyperplasia as compared to monotherapy.